Post-conflict land administration, facilitator of post-conflict state building - Todorovski, D. (2020)
Land and its administration are always negatively affected during conflicts and in post-conflict contexts. This has been confirmed both in the literature and in practice. This research has shown that if land and its administration are neglected or not properly addressed after the end of a conflict, they can be a cause for a renewed armed conflict and an obstacle in the rebuilding of a post-conflict society. The author’s initial research on the topic revealed that there is a relation between land administration and post-conflict state building. Therefore, the main research objective was to identify which interventions in land administration and under which circumstances facilitate postconflict state building.